The Antibacterial Effect of Tinospora Cordifolia (Guduchi) and Its Role in Combating Antimicrobial Resistance - Kavitha EZHILARASU; Anand KASIRANJAN; Shanmuga PRIYA; Anand KAMARAJ (Medeniyet Medical Journal)
Objective: Tinospora cordifolia, often known as 'Guduchi,' has a variety of medicinal characteristics, including those that are anti-diabetic, antiinflammatory, anti-periodic, anti-arthritic, anti-oxidant, anti-allergic, and anti-stress. Drug development projects face significant obstacles because of the rapid rise in antimicrobial drug resistance in the world healthcare system and the introduction of multidrug-resistant (MDR) strains. In order to combat the MDR infections isolated from patients' bodies, the current study was conducted to evaluate and investigate the antibacterial capabilities of Tinospora cordifolia. Methods: Using the agar well diffusion method, Tinospora cordifolia extracts (aqueous, chloroform, and ethanol) were tested for their antibacterial effectiveness against 30 MDR pathogens, and the 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay was used to determine the minimal inhibitory concentration. To determine whether there were any medicinally useful and significant bioactive ingredients in the plant extract, phytochemical analysis was performed. Results: In comparison to the aqueous extract which had little effect, the antibacterial activity of ethanol and chloroform extracts exhibited a potential antimicrobial effect against most of the tested bacterial isolates. Phytochemical analysis of Tinospora cordifolia extract showed alkaloids, carbohydrates, phytosterols, saponins, tannins, proteins, flavonoids, and terpenoids. Conclusions: Our findings show that Tinospora cordifolia plays a potential role in combating the antimicrobial resistance of clinical isolates.